1973
DOI: 10.2134/agronj1973.00021962006500040007x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yields with Direct and Residual Nitrogen Fertilization1

Abstract: The objective of this research was to determine the effect on soybean (Glycine max (L.) Merrill) yields of N added at different rates by different times and methods of application, as direct and residual, and as inorganic and organic sources. A number of studies were conducted over a period of several years at 10 field locations in Illinois. Nitrogen at rates up to 360 kg/ha added for corn (Zea mays L.) the preceding year had no effect on soybean yields. Neither were soybean yields increased by organic sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
2
2

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 9 publications
4
39
2
2
Order By: Relevance
“…In contrast, McCoy (2016) observed 2.5% greater seed yield with PCU compared to urea + NBPT in Mississippi. Welch et al (1973) found that N application method (plow-down, disked-in, side-dressed) had no effect on soybean seed yield for N application at either early flowering or pod-filling stage in Illinois.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, McCoy (2016) observed 2.5% greater seed yield with PCU compared to urea + NBPT in Mississippi. Welch et al (1973) found that N application method (plow-down, disked-in, side-dressed) had no effect on soybean seed yield for N application at either early flowering or pod-filling stage in Illinois.…”
Section: Introductionmentioning
confidence: 90%
“…Wood et al (1993) concluded that applying N fertilizer at R5 was more reliable for increasing seed yield than applying at R1. However, no differences in seed yield were reported for N application at early flowering or pod filling (Welch et al, 1973), nor at V4 and R3 (McCoy, 2016). Barker and Sawyer (2005) found no differences in soybean seed yield due to N source (polymer coated urea [PCU] or urea) and N placement (broadcast or banded) in Iowa, as did Osborne and Riedell (2006b) for ammonium nitrate or urea, Welch et al (1973) for organic or inorganic fertilizers, Wesley et al (1998) for urea ammonium nitrate (UAN), ammonium nitrate (AN), urea, urea + NBPT (N-(n-butyl) thiophosphoric triamide) urease inhibitor, and Schmitt et al (2001) for urea or PCU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil applications of N provided no yield advantage regardless of N source including NH 4 NO 3 (ammonium nitrate) (Welch et al, 1973), NaNO 3 (sodium nitrate) (Deibert et al, 1979), (NH 4 ) 2 SO 4 (ammonium sulfate) (Chesney, 1973;Pal and Saxena, 1976), CO(NH 2 ) 2 (urea) (Flavio et al, 2003;Schmitt et al, 2001), or polymer-coated CO(NH 2 ) 2 (Schmitt et al, 2001). Application methods (broadcast, sidedress, or banding), timing (planting or R1 through R5) (Fehr and Caviness, 1977), and rates (0 to 200 kg ha -1 ) did not improve soybean yields (Chesney, 1973;Deibert et al, 1979;Flavio et al, 2003;Hoeft et al, 2000;Pal and Saxena, 1976;Varco, 1999).…”
mentioning
confidence: 99%
“…Also, in Illinois mineral N fertilization had not effects on soybean yields even in cases of band fertilization close to soybean rows. Also, N fertilization was superfluous for maize in soybean-maize rotation (Welch et al, 1973). However, the experiences from USA are not possible to applying in less fertile soils of middle and eastern Europe.…”
Section: Nitrogenmentioning
confidence: 99%